Creating a Linux Based Home Cloud & Media Service by using Raspberry Pi 3 - Vadnai, Bence; Shaw, Edwin; Erdei, Timotei István (Recent Innovations in Mechatronics, 2018)
Nowadays the microcontrollers are getting cheaper and easier to configure. In my project I am going to show you the best ways to share the data at home between your devices. My goal was to create a home cloud service with some extras only using some old laptop HDDs and a Raspberry PI.